Glutathione and glutathione reductase: a boon in disguise for plant abiotic stress defense operations - Gill, Sarvajeet Singh (2018)
Abiotic stresses such as salinity, drought, clilling, heavy metal are the major limiting factors for crop productivity. These stresses induce the overproduction of reactive oxygen species (ROS) which are highly reactive and toxic, which must be minimized to protect the cell from oxidative damage. The cell organelles, particularly chloroplast and mitochondria are the major sites of ROS production in plants where excessive rate of electron flow takes place. Plant cells are well equipped to efficiently scavenge ROS and its reaction products by the coordinated and concerted action of antioxidant machinery constituted by vital enzymatic and non-enzymatic antioxidant components. Glutathione reductase (GR, EC 1.6.4.2) and tripeptide glutathione (GSH, γ-Glutamyl-Cysteinyl-Glycine) are two major components of ascorbate-glutathione (AsA-GSH) pathway which play significant role in protecting cells against ROS and its reaction products-accrued potential anomalies. Both GR and GSH are physiologically linked together where, GR is a NAD(P)H-dependent enzymatic antioxidant and efficiently maintains the reduced pool of GSH - a cellular thiol. The differential modulation of both GR and GSH in plants has been widely implicated for the significance of these two enigmaticantioxidants as major components of plant defense operations. Considering recent informations gained through molecular-genetic studies, the current paper presents an overview of the structure, localization, biosynthesis (for GSH only), discusses GSH and GR significance in abiotic stress (such as salinity, drought, clilling, heavy metal)-exposed crop plants and also points out unexplored aspects in the current context for future studies.